Artificial Intelligence in Biomedical Applications of Zirconia - Luo, Feng; Hong, Guang; Wan, Qianbing (Frontiers in Dental Medicine, 2021)
Artificial intelligence (AI) is a branch of computer science concerned with building intelligent software or machines capable of performing tasks that typically require human intelligence. Machine learning (ML) addresses the question of how to build computers that improve automatically through experience. AI and ML are today’s most rapidly growing technical fields, lying at the intersection of computer science and statistics and the core of artificial intelligence and data science. Zirconia has drawn lots of attention in dentistry due to its excellent biocompatibility, aesthetically pleasing, high corrosion resistance, and the absence of reported allergic reactions. AI techniques in zirconia-related research and clinical applications have attracted much attention due to their ability to analyze data and reveal correlations between complex phenomena. The AI applications in the field of zirconia science vary according to the application direction of zirconia. This article focuses on AI in biomedical applications of zirconia in dental devices and AI in zirconia-related applications in dentistry.